Short-term weather patterns influence avian body condition during the breeding season - McCloy, Michael W. D.; Grace, Jacquelyn K. (Frontiers in Ecology and Evolution, 2023)
Despite a large body of literature investigating the effects of long-term climate trends on birds, the effects of short-term weather on individual body condition are less established. Poor body condition is associated with declines in individual fitness for many avian species, thus changes to body condition may result in altered population productivity. We utilized a large existing dataset from the Monitoring Avian Productivity and Survivorship program to analyze the effects of daily maximum temperature, daily minimum temperature, and monthly precipitation on avian body condition over a 15-year period across 79 sampling sites in the southeastern United States. We used a model selection approach with generalized additive models at both species and guild levels and found largely nonlinear responses of avian body condition to weather variables. For many species and guilds, a threshold effect was evident, after which the relationship between body condition and weather changed drastically. As extreme weather becomes more common under climate change, species will be pushed further towards or away from these thresholds. Non-linear effects were also highly species-specific and not easily explained by expected effects on food availability. Thus, avian responses to altered weather may be difficult to predict across species. We discuss the implications of these results for individual fitness and population productivity.